Intelligent Network in the Republic of Croatia - Šarić, Slavko; Mikula, Miroslav; Begović, Mladen (Promet - Traffic&Transportation, 2012)
The introduction of intelligence into the telecommunicationnetwork of Croatia is becoming one of the key elements ofthe future development of the network. The paper describes there-organisation of the telecommunication network in Croatia,the process of creating and managing the intelligent services,the initial situation and the feasible plan of introducing the INconcepts. The paper is concluded with a list of IN services thatare being introduced in the initial phase of the Croatian telecommunicationnetwork.